PEMBELAJARAN DALAM JARINGAN (DARING) SAAT DAN PASCA PANDEMI COVID-19 - Aji Permana Putra; Hema Malini (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan Universitas Cokroaminoto Yogyakarta, 2022)
Learning during the pandemic is carried online by paying attention to the situation and conditions when the Covid-19 outbreak hit the whole world. From the results of the study, it was found that the online learning models that are widely used are WAG (Whatsapp Group), Google For Education (Google Form, Google Classroom, Google Drive), Youtube, Zoom Meeting. The obstacles experienced were unstable communication signals, running out of internet quota, parents' cellphones being brought to work, students accompanied by their parents doing homework at night. While the advantages of online learning are flexible, complete reference sources, and adaptive to technology. Online learning bridges between students and teachers so that learning can still take place even though in different places. This shows that the role of technology dominates in the field of education. Compared to before the use of online learning, conventional learning still prioritizes face-to-face and manual use of equipment such as blackboards, markers, erasers and text books and note books. The development of education in industry 4.0 must be accelerated quickly, especially in the development of education which should no longer discuss the use of technology but rather the development of technology in the use of education, for example in online learning which should be more effective in the implementation of learning. the industry must be a real solution in maximizing education during a pandemic and post-pandemic by developing knowledge in the use of technology.